Scientific Discussions with American Political Scientists from Stanford on Issues of European Security (Czech Journal of International Relations, 1992)
In mid-December 1990, at the invitation of the úMV, prominent American political scientists from the Center for International Security and Arms Control at Stanford University in California visited Prague. The delegation was led by professor dr. William Perry, co-director of the center and former undersecretary for research and technology at the US Department of Defense. Its members were professor dr. Michael May, a scientist at the center, and the former director of the Lawrence Livermore National Laboratory for Nuclear Weapons, and professor dr. Robert Hamerton-Kelly, the center's project coordinator.On December 17 and 18, 1990, the ÚMV held a scientific discussion on current issues of European security with their participation. In addition to the employees of the institute, she is also a member of the Czechoslovak party. attended by doc. dr. Alexandr Ort, DrSc., and then Maj. Gen. ing. Jaroslav Štecha and Col. ing. Jaroslav Němec from FMO. At the suggestion of the American side, the discussion was divided into four thematic areas:1. General European issues.2. Security issues.3. Weapons conversion.4. Ethnic minorities and European security.